3D Printed Functionalized Nanocellulose as an Adsorbent in Batch and Fixed-Bed Systems - Mohd Shaiful Sajab; Wan Nazihah Liyana Wan Jusoh; Denesh Mohan; Hatika Kaco; Rubiyah Baini (MDPI, 2024)
Indexed by WOS/Scopus/ERA